2006
DOI: 10.1161/circulationaha.105.000398
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Valve Repair Versus Revascularization Alone in the Treatment of Ischemic Mitral Regurgitation

Abstract: Background— For patients with ischemic mitral regurgitation (MR), it is not clear whether adjunctive mitral valve (MV) repair at the time of coronary artery bypass graft surgery (CABG) is beneficial. We sought to test the hypothesis that MV repair with CABG is superior to CABG alone in improving MR without increasing operative or long-term mortality. Methods and Results— A total of 107 consecutive patients with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 24 publications
3
102
0
2
Order By: Relevance
“…Some authors consider that correction of mitral insufficiency does not stop the progression of left ventricular remodeling and has no effect on survival. Moreover, there is only additional unreasonable surgical risk [13,20]. Several studies have shown that one third of patients has recurrnet mitral insufficiency after mitral valve repair up to preoperative level within 3-5 years after surgery [14,23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some authors consider that correction of mitral insufficiency does not stop the progression of left ventricular remodeling and has no effect on survival. Moreover, there is only additional unreasonable surgical risk [13,20]. Several studies have shown that one third of patients has recurrnet mitral insufficiency after mitral valve repair up to preoperative level within 3-5 years after surgery [14,23].…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, revascularization of ischemic areas improves regional contractility that reduces severity of MR without need for its correction [11,28]. Moreover, several studies have shown that isolated coronary artery bypass grafting in patients with CAD and moderate MR does not affect long-term survival or functional status [19,20,24,26]. Data of 465 publications devoted to treatment of ischemic MR I-II were analyzed in large observational trial by A. Srivastavaa et al [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the additional risk of mitral valve surgery is not negligible, particularly in patients with comorbidities and poor LV function. Very ill patients or elderly individuals with a history of atrial fibrillation might be treated conserva tively with revascularization alone or with a percutaneous approach, 39 although the treatment strategy also depends on the individual's risk profile.…”
Section: Secondary Mrmentioning
confidence: 99%